2020
DOI: 10.4103/jrms.jrms_476_20
|View full text |Cite
|
Sign up to set email alerts
|

Current status of COVID-19 pandemic; characteristics, diagnosis, prevention, and treatment

Abstract: Humans have always been encountered to big infectious diseases outbreak throughout the history. In December 2019, novel coronavirus (COVID-19) was first noticed as an agent causing insidious pneumonia in Wuhan, China. COVID-19 was spread rapidly from Wuhan to the rest of the world. Until late June 2020, it infected more than 10,000,000 people and caused more than 500,000 deaths in almost all of countries in the world, creating a global crisis worse than all previous epidemics and pandemics. In the current revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…These results represent the first symptom weighting in a population-based screening in Mexico with no exclusion criteria and limitations established by the operational definition established in the Mexican health guidelines. In the same way, differences in the proportions of COVID-19-related symptoms between other studies and ours ( Table 5 ) [ 18 , 19 , 20 ], indicated the importance of expanding the range of symptoms and maintaining updated over time the operational definition in the Mexican health surveillance system.…”
Section: Discussionsupporting
confidence: 58%
“…These results represent the first symptom weighting in a population-based screening in Mexico with no exclusion criteria and limitations established by the operational definition established in the Mexican health guidelines. In the same way, differences in the proportions of COVID-19-related symptoms between other studies and ours ( Table 5 ) [ 18 , 19 , 20 ], indicated the importance of expanding the range of symptoms and maintaining updated over time the operational definition in the Mexican health surveillance system.…”
Section: Discussionsupporting
confidence: 58%
“…Molecular assay was thought to be the gold standard for COVID-19 confirmation, but a lot of studies showed that COVID-19 patients may have initial reverse transcriptase polymerase chain reaction (RT-PCR) negative results (3,4). The false negative results occurred frequently although reasons for false negatives of the molecular assay were found to relate to disease course, having insufficient cellular material for detection, and improper extraction of nucleic acid from clinical materials (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…It is named because of the presence of crown-like spikes glycoprotein on its surface. The capability to infect multiple hosts and the cause of different diseases despite indicating acute respiratory infections in humans make this virus a complex pathogen [5] , [6] . The genomic sequence of SARS-CoV-2 shows close relation with bat-SL-CoVZC45 and bat-SL-CoVZXC21; its receptor-binding domain is similar to SARS-CoV, according to homology modeling [7] .…”
Section: Characteristics Of Sars-cov-2 and Covid-19mentioning
confidence: 99%